2014
DOI: 10.1186/preaccept-1491812025142774
|View full text |Cite
|
Sign up to set email alerts
|

Response assessment in metastatic melanoma treated with ipilimumab and bevacizumab: CT tumor size and density as markers for response and outcome

Abstract: Background: Investigate the tumor diameter and density changes in advanced melanoma patients treated with ipilimumab plus bevacizumab, compare response rates based on different response criteria, and study association between these measures and survival. Methods: Twenty-one advanced melanoma patients with 59 measurable lesions treated in a phase 1 trial of ipilimumab plus bevacizumab were retrospectively studied. Tumor diameter and density were measured on baseline and first follow-up CT. Responses were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…While tumor volume is initially reduced by chemotherapy in over half of patients, responses are not durable and progression typically occurs within 3 months of starting chemotherapy . Conversely, multiple trials of immune checkpoint inhibitors in skin cancers have proven to be effective and there is evidence that they are most effective when disease burden is small . This highlights the importance of using MCC‐specific metastatic patterns to detect disease spread early and provide rescue therapies before patients developed more extensive disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While tumor volume is initially reduced by chemotherapy in over half of patients, responses are not durable and progression typically occurs within 3 months of starting chemotherapy . Conversely, multiple trials of immune checkpoint inhibitors in skin cancers have proven to be effective and there is evidence that they are most effective when disease burden is small . This highlights the importance of using MCC‐specific metastatic patterns to detect disease spread early and provide rescue therapies before patients developed more extensive disease.…”
Section: Discussionmentioning
confidence: 99%
“…13,23 Conversely, multiple trials of immune checkpoint inhibitors in skin cancers have proven to be effective 15,20,24,25 and there is evidence that they are most effective when disease burden is small. 26 This highlights the importance of using MCCspecific metastatic patterns to detect disease spread early and provide rescue therapies before patients developed more extensive disease. In our cohort, the median time to first recurrence was less than a year, suggesting more frequent surveillance during this period could detect metastases earlier and improve the rate and/or duration of responses to immunotherapy.…”
Section: F I G U R E 3 a Comparison Of Sites Of Initial Distant Metamentioning
confidence: 99%
“…In support of this notion, higher pretreatment VEGF serum levels are associated with shorter overall survival times in melanoma patients treated with the immune checkpoint inhibitor ipilimumab, a mAb that blocks cytotoxic T lymphocyte antigen 4 (CTLA4) . Moreover, regimens combining ipilimumab (anti‐CTLA4) and bevacizumab (anti‐VEGF) are being evaluated in patients with melanoma and glioblastoma . These studies have demonstrated that the combination of bevacizumab (anti‐VEGF) and ipilimumab (anti‐CTLA4) can be safely administered with predictable and manageable toxicity.…”
Section: The Immune Effects Of Growth Factorsmentioning
confidence: 94%
“…25 Moreover, regimens combining ipilimumab (anti-CTLA4) and bevacizumab (anti-VEGF) are being evaluated in patients with melanoma and glioblastoma. [26][27][28][29] These studies have demonstrated that the combination of bevacizumab (anti-VEGF) and ipilimumab (anti-CTLA4) can be safely administered with predictable and manageable toxicity. Moreover, these studies illustrate that the combination of bevacizumab and ipilimumab can augment endothelial cell activation, lymphocyte infiltration into tumors, cytokine and chemokine expression, and antimelanoma humoral responses.…”
Section: The Immune Effects Of Growth Factorsmentioning
confidence: 99%
“…Using observe the results of using AAT [6][7][8]. The prediction of its antitumor effectiveness beforehand using math ematical simulation could be attempted.…”
Section: Investigation Of the Effects Of Angiogenesis On Tumor Growthmentioning
confidence: 99%